HOW PERIPHERIES TALK TO EACH OTHER, OR THE THEORY OF POSTCOLONIALISM WITHOUT A “CENTRE” - Gundorova, Tamara (Porównania, 2014)
The alternative conceptions of postmodernism developing by Latin-American philosophers – transmodernity by Enrique Dussel and decolonization by Walter Mignolo and Rolando Vázquez who criticize eurocentrism are analyzed in the arcticle. Another point raised in the article is the analysis of a colonial character of the cultural utopian view of Johann Herder who constructed Ukraine as an European Other. The article shows the necessity of the inclusion of Ukraine into the dialogue of alternative postcolonial practices spread horizontally, on peripheries, from Latin America to Eastern Europe.